Are Forecast Updates Progressive? - Chia-Lin Chang; Philip Hans Franses; Michael McAleer (Tinbergen Institute, 2013)
Many macroeconomic forecasts and forecast updates like those from IMF and OECD typically involve both a model component, which is replicable, as well as intuition, which is non-replicable. Intuition is expert knowledge possessed by a forecaster. If forecast updates are progressive, forecast updates should become more accurate, on average, as the actual value is approached. Otherwise, forecast updates would be neutral. The paper proposes a methodology to test whether macroeconomic forecast updates are progressive, where the interaction between model and intuition is explicitly taken into account. The data set for the empirical analysis is for Taiwan, where we have three decades of quarterly data available of forecasts and their updates of the inflation rate and real GDP growth rate. Our empirical results suggest that the forecast updates for Taiwan are progressive, and that progress can be explained predominantly by improved intuition.
urn:NBN:nl:ui:15-1765/39434
Keywords: C53; C22; E27; E37; 330; Macroeconomic forecasts; econometric models; intuition; progressive forecast updates; forecast errors; Konjunkturprognose; Ökonometrisches Modell; Zeitreihenanalyse; Schätzung; Taiwan